Secret Agent Jack Stalwart. [book 8], Peril at the Grand Prix: Italy - Singer Hunt, Elizabeth (Red Fox, 2006)
Destination: Italy. Jack's car-racing hero, Morgan Parks, is in danger. Someone has already tried to kill him once, and they're about to try again. Can Secret Agent Jack Stalwart save his idol and the Italian team's chance to win the Monza Grand Prix?